2020
DOI: 10.3389/fphys.2020.590262
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Activated Chloride Channel ANO1/TMEM16A: Regulation of Expression and Signaling

Abstract: Anoctamin-1 (ANO1), also known as TMEM16A, is the most studied member of anoctamin family of calcium-activated chloride channels with diverse cellular functions. ANO1 controls multiple cell functions including cell proliferation, survival, migration, contraction, secretion, and neuronal excitation. This review summarizes the current knowledge of the cellular mechanisms governing the regulation of ANO1 expression and of ANO1-mediated intracellular signaling. This includes the stimuli and mechanisms controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 96 publications
(144 reference statements)
1
18
1
1
Order By: Relevance
“…Although it has been recently reported that TMEM16A activated EGFR signaling pathway in HNSCC, breast cancer and pancreatic cancer (15,30,31,50,51). However, in this study, we did not find that TMEM16A was significantly associated with EGFR in human CRC tissues.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Although it has been recently reported that TMEM16A activated EGFR signaling pathway in HNSCC, breast cancer and pancreatic cancer (15,30,31,50,51). However, in this study, we did not find that TMEM16A was significantly associated with EGFR in human CRC tissues.…”
Section: Discussioncontrasting
confidence: 92%
“…For example, TMEM16A mRNA expression might be regulated by other factors such as hypermethylation of the TMEM16A promoter, the signal transducer and activator of transcription (STAT) and some soluble factors in the tumor micro-environment at the transcriptional level during lymph node metastasis. TMEM16A expression might be controlled by a number of microRNAs such as miR-9, miR-144, and miR-132 at translational level, as previously reported ( 13 , 26 , 52 ). TMEM16A protein might interact with other molecular targets including ERK1/2, AKT, camodulin kinase II (CaMKII), EGFR, secreted calcium-activated chloride channel regulator 1 (CLCA1), and Coatomer protein complex subunit beta 1 (COPB1) at post-translational level.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Huang et al [58] showed that TMEM16C binds the Na +activated K + channel Slack, increasing the single-channel activity and sodium sensitivity of Slack channels; structural data by Pan et al [59] revealed that TMC1 channels share a common architecture with the TMEM16 channel, raising the possibility that some TMCbinding proteins could also bind TMEM16F; Avalos-Prado et al [60] reported that KCNE1 is an auxiliary subunit of TMEM16A. However, also several other modulators including cholesterol, fatty acids, phosphorylation, have been shown to regulate the activity of some TMEM16 family members [4,61].…”
Section: Ion Selectivitymentioning
confidence: 99%
“…Основными физиологическими эндогенными факторами, вызывающими увеличение экспрессии TMEM16А, являются интерлейкины, эпидермальный фактор роста (epidermal growth factor (EGF) и ангиотензин II [115]. Бактериальный токсин липополисахарид вызывает увеличение экспрессии TMEM16А при развитии рака лёгкого у человека и в альвеолярных эпителиальных клетках мышей [116,117].…”
Section: молекулярные механизмы и взаимодействие с сигнальными путямиunclassified